2015
DOI: 10.1097/pai.0000000000000084
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Genotyping of Somatic Mutations in the EGFR, KRAS, PIK3CA, BRAF Genes from NSCLC Patients Using Hydrogel Biochips

Abstract: Targeted inhibitors of the epidermal growth factor receptor (EGFR) are used for the treatment of non-small cell lung cancer (NSCLC). Somatic mutations in the EGFR gene and key effectors of the EGFR-signaling pathway (KRAS, BRAF, PIK3CA) are associated with sensitivity to these drugs. We developed a highly sensitive LUNG CANCER (LC)-biochip approach for the detection of the most common EGFR, KRAS, PIK3CA, and BRAF gene mutations. The locked nucleic acid clamp PCR technique was used to increase the sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, and can be further classified as nonsquamous carcinoma (including adenocarcinoma, which accounts for 40% of NSCLCs) and squamous NSCLC, which makes up 30% of NSCLC cases [ 2 4 ]. Inhibitors of the epidermal growth factor receptor (EGFR) are used for the treatment of NSCLC [ 5 ]. In addition, other inhibitors such as miR-99a and heat shock protein 90 (HSP 90) have been also involved in lung tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, and can be further classified as nonsquamous carcinoma (including adenocarcinoma, which accounts for 40% of NSCLCs) and squamous NSCLC, which makes up 30% of NSCLC cases [ 2 4 ]. Inhibitors of the epidermal growth factor receptor (EGFR) are used for the treatment of NSCLC [ 5 ]. In addition, other inhibitors such as miR-99a and heat shock protein 90 (HSP 90) have been also involved in lung tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…In this proof-of-concept work, it was shown that peptide hydrogel architecture provides a rational design for responsive peptide-based hydrogels. 72,73 Some biosensors built with hydrogel systems have been studied, for example, the biochips for somatic mutation in genes detection, 74 microfluidic devices sensitive to metalloproteinases that regulates the composition of an extracellular matrix and are correlated to some vascular disease, cancer progression, and bone disorders. 41 In this sense, the opportunity of using hydrogels for antigens encapsulation can motivate the design of novel devices for disease diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…The hybridization and image analysis were performed as described before [ 61 ]. Briefly, hybridization was performed in 40 μl of 25% formamide (Serva, Oklahoma City, USA), 6× saline-sodium phosphate-EDTA (Promega, Fitchburg, USA) and 20 μl lebeled PCR products.…”
Section: Methodsmentioning
confidence: 99%
“…The high sensitivity has been reached by combining, in one assay, the LNA PCR clamp technique and the mutation-specific hybridization on a hydrogel biochip, which allows the identification of somatic mutations in a large excess of wild type (WT) DNA. Previously, this approach has been developed and applied for the analysis of somatic mutations in EGFR, KRAS, BRAF, PI3K genes in lung cancer cells [ 61 ].…”
Section: Introductionmentioning
confidence: 99%